Enhancing lung transplantation with ECMO: a comprehensive review of mechanisms, outcomes, and future considerations - Pervaiz Butt Salman; Kakar Vivek; Abdulaziz Salman; Razzaq Nabeel; Saleem Yasir; Kumar Arun; Ashiq Fazil; Ghisulal Praveen; Thrush Aaron; Malik Sadaf; Griffin Mairead; Amir Mahanoor; et al. (The Journal of ExtraCorporeal Technology)
Background: Lung transplantation (LTx) is a critical intervention for patients with end-stage lung disease. However, challenges such as donor organ scarcity and post-transplant complications significantly affect its success. Recent advancements in Extracorporeal Membrane Oxygenation (ECMO) have shown promise in improving the outcomes and expanding eligibility for LTx. Methods: A comprehensive literature review was conducted, focusing on studies that explore the use of ECMO in lung transplantation. A thorough search of relevant studies on ECMO and LTx was conducted using multiple scholarly databases and relevant keywords, resulting in 73 studies that met the inclusion criteria. Sources included peer-reviewed journals and clinical trial results, with emphasis on articles captured recent advancements in ECMO technology and techniques. Results: ECMO has been crucial in supporting patients before, during, and after LTx. It serves as a bridge to transplantation by maintaining pulmonary and circulatory stability in critically ill patients awaiting donor organs. ECMO also aids in the evaluation of marginal donor lungs and supports patients through acute post-transplant complications. Recent technological advancements have improved the safety and efficacy of ECMO, further solidifying its role in LTx. Conclusion: In conclusion, this review underscores ECMO's critical role in enhancing outcomes across all stages of lung transplantation. Its various configurations and strategies have shown promise in stabilizing critically ill patients and improving transplant success rates. Looking ahead, it’s important to gather more information about the long-term outcomes and potential complications associated with ECMO use. More research and data collection will help us understand the benefits and risks better, leading to improved decision-making and patient care in this field.